(untitled) (Journal of Medical & Health Sciences Review, 2025)
Background: Obstetric anal sphincter injuries (OASI), remain a major complication of vaginal childbirth. A reduced perineal body length (PBL) suggested as an important risk factor for OASI. Objective: To determine whether short PBL is associated with a higher likelihood of OASI in primigravida delivering vaginally with episiotomy. Methods: This study was carried out in the Department of Obstetrics & Gynecology, Sir Ganga Ram Hospital, Lahore,from 1 April 2025 to 3 July 2025 . A total of 60 primigravida were recruited, divided into Group A with short PBL (≤3.0 cm, n=30) and Group B with longer PBL (>3.0 cm, n=30). Incidence of OASI was compared between groups, with additional stratified analyses performed for maternal age, body mass index (BMI), and neonatal birth weight. Data were analyzed using SPSS version 25. Results: Mean PBL was significantly shorter in Group A (2.8 ± 0.1 cm) than in Group B (3.5 ± 0.2 cm, p < 0.001). OASI occurred more frequently in women with short PBL—third-degree tears in 50% and fourth-degree in 23.3%—compared with 16.7% and 0% in Group B (p < 0.001). Subgroup analyses indicated that women aged ≤25 years, those with BMI ≥25 kg/m², and those delivering infants >3.5 kg were at greater risk of OASI when PBL was short. Conclusion: Shorter PBL is significantly associated with a higher incidence of OASI in primigravida women undergoing episiotomy-assisted vaginal delivery. Routine prenatal measurement of PBL, combined with consideration of maternal and fetal factors, could help in planning targeted preventive measures to reduce severe perineal trauma.